Sostenibilitat i modalitats turístiques. Una anàlisi de casos a Catalunya - Torres Delgado, Anna (Documents d’Anàlisi Geogràfica, 2011)
The aim of this paper is to present the results for the implementation of a set of indicators of social-cultural, economical and environmental sustainability in different municipalities of Catalonia (Salou, Naut Aran, Tarragona and Llavorsí). The main focus is to evaluate how different tourist modalities (sun and beach tourism, snow tourism, cultural tourism and adventure sport tourism) influence the local tourist sustainability. This is a methodological approach to identify and quantify the tourism impacts at local level to assess comparatively, through case analysis, the level of tourist sustainability associated with each modality.